PENGARUH PROMOSI JABATAN, MUTASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA BANK RAKYAT INDONESIA (PERSERO) Tbk. CABANG SITUBONDO - Karnadi Karnadi; Satrio Wiji Pradana (Relawan Jurnal Indonesia, 2018)
This study aims (1) to determine the effect of job promotion, mutation and work discipline have a partial effect on employee performance (2) to determine the effect of job promotion, mutation and work discipline simultaneously affect the performance of employees (3) to find out between promotions, mutations and work discipline that predominantly affect employee performance. The method used in this study is a quantitative method. The result of the research is multiple linear regression equation Y = -2,811E-16 + 0,310 X1 + 0,288 X2 +0,372 X3 + e. Partially, promotion has a significant positive effect with tcount of 2.665> ttable 2.021, mutation has a significant positive effect with tcount of 2.343> ttable 2.021 and work discipline has a significant positive effect with tcount of 2.820> ttable 2.021. In terms of job promotion, mutation and work discipline have a significant effect on employee performance with a value of Fcount 48,158> Ftable 2,84. The most dominant variable in this study is work discipline with a value of 2.820.